Innovative Strategy for the Application of Discretion in Government Policy in Indonesia: An Analysis - Wibowo, Satrio (Universitas Gorontalo, 2024)
The objective of this study is to recognise the following: discretion as a kind of innovation in government policy application; discretionary criteria as an innovation in government policy carrying the benefit principle; and discretionary models as an innovation in government policy seen to be ideal. This study used a statutory approach in conjunction with a normative legal strategy. The discussion's conclusions demonstrate that, in order to encourage official innovation, discretionary regulation—a kind of government policy innovation—must be implemented. This phase entails rejecting a passivity in the realisation of innovation and pursuing harmony between innovation and legislation. Four factors are taken into consideration while evaluating discretion as a novel government policy: power, constraints, testing, and judicial oversight. The welfare state's core principles must serve as the foundation for the discretionary model that is seen to be best for developing innovative policies that accomplish bureaucratic transformation. Discretionary policies should also encourage collaboration between authorities and adhere to Pancasila's tenets. Moreover, discretionary policies must abide with the fundamentals of good governance (AUPB).